A Study on Various Practices of Management In Distance Education: Exploring the Gap between Technology and Practice in Distance Education (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The number of higher education institutionsaround the world offering distance education programs has increasedsignificantly in the last two decades, and most countries have seen a growth indistance education enrollments. The literature reviewing distance educationtrends, the evolving methods of delivery, and emerging distance technologies isextensive. Even still, the rapid growth of technology in this field ofeducation has outpaced research on practice, design, and models.